Correction: Biofilm microbiome in extracorporeal membrane oxygenator catheters. - Yeuni Yu; Yun Hak Kim; Woo Hyun Cho; Bong Soo Son; Hye Ju Yeo (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0257449.].